Transport of corrosion products in the steam-water cycle of supercritical power plant. (25th February 2017) - Jiang, Dongfang; Xu, Hong; Khan, Hasan Izhar; Zhu, Zhongliang; Deng, Bo; Zhang, Naiqiang
Highlights: Transport of corrosion product is analysed considering the water parameters. The mass balance equation is applied to establish the models of the steam-water cycle. 85% of corrosion products come from the feedwater train and 90% deposit on boiler tubes. A micro-oxygenated treatment method for supercritical power plant is proposed. Abstract: The operational reliability of thermal power plant boilers is significantly influenced by corrosion processes and by the formation of deposits on heat transfer surfaces. The basis of this problem is the transport of corrosion products in the steam-water cycle. In this study, the source of corrosion products was discussed. The effect of the water parameters on the transport of corrosion products was analysed. The generation (or deposition) ratio of corrosion products on the main components was evaluated. The corrosion of carbon steel was found to be the main source of transported corrosion products, wherein about 85% of the corrosion products transferred in the fluid was derived from the feed-water train and about 90% of the corrosion products deposited on the boiler tubes. Consequently, a micro-oxygenated treatment method for supercritical power plant was proposed to restrain the transport of corrosion products.